2022
DOI: 10.3389/fonc.2022.958869
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 inhibitors plus lenvatinib versus PD-1 inhibitors plus regorafenib in patients with advanced hepatocellular carcinoma after failure of sorafenib

Abstract: BackgroundLenvatinib, regorafenib and anti-programmed cell death protein-1 (PD-1) immunotherapy have shown promising clinical outcomes in patients with advanced hepatocellular carcinoma (HCC) after sorafenib failure, respectively. However, the combination of the two treatments has not been reported. We compared the efficacy of PD-1 inhibitors with lenvatinib (PL) and PD-1 inhibitors plus regorafenib (PR) in patients with advanced HCC in this study.MethodsWe conducted a retrospective study of advanced HCC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…In this work, the median OS of patients who received TACE plus rst-line TKI plus PD-1 inhibitors was 15.0 months, consistent with prior work that revealed an OS of 14.9 months. The median PFS of these patients was 11.0 months in the present study, which was greater than that observed in a previous study that reported a PFS of 4.2 months [22]. This difference in PFS might be explained by variations in baseline patient characteristics: the previous trial included a larger proportion (88.4%) of patients with liver cirrhosis (only 52.1% in our study).…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In this work, the median OS of patients who received TACE plus rst-line TKI plus PD-1 inhibitors was 15.0 months, consistent with prior work that revealed an OS of 14.9 months. The median PFS of these patients was 11.0 months in the present study, which was greater than that observed in a previous study that reported a PFS of 4.2 months [22]. This difference in PFS might be explained by variations in baseline patient characteristics: the previous trial included a larger proportion (88.4%) of patients with liver cirrhosis (only 52.1% in our study).…”
Section: Discussioncontrasting
confidence: 86%
“…However, for these patients, the survival obtained by PD-1 inhibitor monotherapy is still unsatisfactory [19]. Thereby, PD-1 inhibitors in combination with other treatments (such as TACE and TKI) are being considered for these uHCC patients during second-line therapy; for instance, a recent study suggested that, as the second-line therapy for uHCC patients, PD-1 inhibitors in combination with rst-line TKI (e.g., sorafenib) can prolong the survival time (i.e., the median OS can reach 14.1 months and the median PFS can reach 5.3 months) [22].…”
Section: Introductionmentioning
confidence: 99%
“…First, patient eligibility is restricted with only those meeting the current inclusion criteria (limited to cases with a Child–Pugh A score) being considered, primarily because of the occurrence of severe immune-related adverse events resulting from the long half-life and off-target effects of mAbs. , Second, the high cost of treatment is rooted in the complexity of mAb production. , Consequently, recent clinical studies have shown a growing inclination toward the incorporation of more cost-effective small-molecule inhibitors. Thus, the combination of small-molecule TKIs with antiangiogenesis properties, such as apatinib (Apa), regorafenib, or lenvatinib, with mAb targeting of PD-1/PD-L1, has displayed enhanced antitumor efficacy in clinical trials for treating advanced HCC. Certainly, the contrasting physicochemical properties inherent to these two types of drugs produce distinct pharmacokinetic profiles. Consequently, when employed concurrently, this divergence in their pharmacokinetics may result in a notable delay in achieving the desired therapeutic effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid cancer, kidney cancer, liver cancer, and endometrial cancer have all been treated with lenvatinib on a large scale. 18 , 19 Although the overall survival (OS) of lenvatinib was not inferior to that of sorafenib (13.6 months vs 12.3 months) according to REFLECT, the progression-free survival (PFS) was significantly better (7.4 months vs 3.7 months, p<0.0001). 20 The NCCN guidelines also recommend that lenvatinib be selected as a second-line treatment for sorafenib-resistant HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: H.R, hazard ratio; CI, confidence interval; ECOG PS, Eastern Cooperative Oncology Group Performance status; AFP, alpha fetoprotein; BCLC, Barcellola Clinic Liver Cancer; HBV, hepatitis B virus; TACE, transarterial chemoembolization; HAIC, hepatic artery infusion chemotherapy.https://doi.org/10.2147/TCRM.S420371DovePressTherapeutics and Clinical Risk Management 2023:19 …”
mentioning
confidence: 99%